The demise of large tropical brachiopods and the Mesozoic marine revolution - Elizabeth M. Harper; Lloyd S. Peck (Royal Society Open Science, 2024)
Changes in predator–prey interactions are often implicated as drivers of major evolutionary change. A prominent example is the dramatic changes in shallow marine assemblages during the Mesozoic Marine Revolution (MMR) when major clades, including rhynchonelliform brachiopods, became restricted and less diverse. Currently, shallow-water temperate and polar brachiopods can be large, but in the tropics, they are small. By contrast, we demonstrate that throughout the Jurassic large brachiopods occurred in shallow sites, from polar to tropical latitudes, but are absent in later periods from tropical areas. These changes occurred in parallel in both major orders (Rhynchonellida and Terebratulida) and also independently within the two sub-ordinal lineages within the Terebratulida (terebratulinids and terebratellinids). Increases in both grazing and predation pressures associated with the MMR might account for this pattern. However, we note that many current environments support both large brachiopods and high densities of grazing species and suggest that the pattern fits more closely to the intensification of durophagous predation in shallow tropical waters.